Perbaikan Tegangan Pada Jaringan Distribusi 20 Kv Melalui Penempatan Pembangkit Tersebar Berbasis Particle Swarm Optimization - Yuli Asmi Rahman; Sitti Nuradha Wati S; Ratih Mar’atus Shalihah; Irwan Mahmudi (Universitas Islam Lamongan, 2022)
Voltage losses are problems that often occur in distribution systems, resulting in voltage drops to reduce the electrical power supplied to consumers. The allowable stress drop in the distribution is +5% and -10%. One way to overcome this is to place scattered power plants into account the given location and capacity (MW and MVar). In this study, optimization of generator placement using an effective method is Particle Swarm Optimization (PSO). PSO is an algorithm that implements problem understanding. The sequence of news generators is carried out by directing the selection of Gbest, which has a minimum voltage drop value by increasing the number of particles. Initial simulation using a power flow study run via Matlab and ETAP. The objective function of this optimization process is drop voltage minimization with contraint function is the power loss of each bus. The final simulation found the best generator locations on buses 7, 10, and 13. After optimization, the voltage increase was obtained by 4.05%, 9.05%, and 10.15% on each bus.